Composite-alumina-carbon molecular sieve membranes prepared from novolac resin and boehmite. Part I: Preparation, characterization and gas permeation studies - Margot A. Llosa Tanco (2015)
Supported composite alumina-carbon molecular sieve membranes (c-CMSM) were prepared from in house prepared novolac phenolic resin loaded with boehmite nanoparticles in a single dipping-drying-carbonization step. A porous a-alumina tube support was dipped into a N-methyl-2-pyrrolidone solution containing polymerized novolac resin loaded with boehmite, subsequently dried at 100 degrees C and carbonized at 500 degrees C under nitrogen environment. The structure, morphology and performance of the membranes were examined by scanning electron microscopy (SEM), X-ray diffraction (XRD), thermogravimetric analysis (TGA), carbon dioxide adsorption and permeation of N-2, O-2, He, H-2 and CO2. SEM showed carbon membranes with a thin and very uniform layer with a thickness of ca. 3 mu m CO2 adsorption isotherms indicated that the produced carbon membranes presented a microporous structure. The c-CMSM exhibited good gas separation properties. The permselectivity surpass the Robeson upper bound for polymeric membranes, especially regarding ideal permselectivities of pairs H-2/N-2 = 117, and He/O-2 = 49. Aging effects were observed after membrane exposure to ambient air. However with a thermal treatment under nitrogen atmosphere the permeance of nitrogen increases. Copyright (C) 2015, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.